Utilization of technology-based learning media in junior high school mathematics learning: A systematic literature review - I Gede Danur Prabawa Semara; Raphita Yanisari Silalahi; I Wayan Puja Astawa (Priviet Social Sciences Journal, 2026)
This study aimed to examine and synthesize research findings on the utilization of technology-based learning media in junior high school mathematics learning. This study employed a Systematic Literature Review (SLR) approach following PRISMA guidelines to ensure a systematic, transparent, and replicable process. Data were collected from the Google Scholar, Garuda, and Sinta databases, resulting in 17 selected articles out of an initial 32,100 records after a rigorous screening process. The findings indicate that technology-based learning media, such as interactive multimedia, instructional videos, Android-based applications, and virtual laboratories, have a positive impact and are generally considered valid, practical, and effective for improving students’ conceptual understanding, motivation, engagement, and learning outcomes. The research methods identified include Research and Development (R&D) as the most dominant approach, as well as quantitative, qualitative, and community service or Pengabdian Kepada Masyarakat (PKM) studies. These media have been applied to various mathematics topics, including algebra, geometry, arithmetic, and statistics. However, most studies are limited by short implementation periods and small sample sizes, and they tend to focus more on product development rather than on long-term impacts or higher-order thinking skills. Therefore, future research should examine long-term effects and develop more innovative, student-centered learning approaches that promote critical thinking and problem-solving skills.